2022
DOI: 10.20870/productions-animales.2022.35.1.5498
|View full text |Cite
|
Sign up to set email alerts
|

De l’animal au territoire, regards sur l’efficience de l’azote dans les systèmes bovins laitiers

Abstract: Améliorer la valorisation de l’azote à toutes les étapes de son utilisation est une priorité, notamment en élevage où elle demeure relativement faible. Les indicateurs d’efficience azotée sont nombreux et basés sur des méthodes de calculs diverses selon le contexte et les échelles considérées. La littérature illustre un certain nombre de pratiques vertueuses, le plus souvent applicables à l’échelle de l’animal ou du troupeau, qui en améliorent la valorisation. Mais peu d’études présentent une vision intégrativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Comparatively, applying the same dose of organic matter by microdosing and broadcasting would allow the microdose to gain an additional 100% of fertilized area. In the present study, there was no excessive application of nitrogen and hence no negative impacts on the environment [38][39][40]. When compost is applied as top dressing, followed by a slight soil cover, it mixes with the soil and contributes more to the improvement of the nitrogen balance and the sustainability of the system.…”
Section: Sustainability Of the Production Systemmentioning
confidence: 57%
“…Comparatively, applying the same dose of organic matter by microdosing and broadcasting would allow the microdose to gain an additional 100% of fertilized area. In the present study, there was no excessive application of nitrogen and hence no negative impacts on the environment [38][39][40]. When compost is applied as top dressing, followed by a slight soil cover, it mixes with the soil and contributes more to the improvement of the nitrogen balance and the sustainability of the system.…”
Section: Sustainability Of the Production Systemmentioning
confidence: 57%
“…This hypothesis justifies a study of the chemical composition of each herbaceous species. Godinot et al (2022) showed that nitrogen levels are always higher in grazed situations at the end of winter. According to them, animals graze on average younger leaves than those observed in protected areas since grazing occurs daily.…”
Section: Effect Of Grazing On the Chemical Composition Of Fallow Fieldsmentioning
confidence: 98%